2020
DOI: 10.1038/s41593-020-0679-6
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes contribute to remote memory formation by modulating hippocampal–cortical communication during learning

Abstract: The consolidation and retrieval of remote memories depend on the coordinated activity of the hippocampus and frontal cortices. However, the exact time at which these regions are recruited to support memory and the interactions between them are still debated. Astrocytes can sense and modify neuronal activity with great precision, but their role in cognitive function has not been extensively explored. To investigate the role of astrocytes in remote memory we expressed the Gi-coupled receptor hM4Di in CA1 astrocy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
218
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(230 citation statements)
references
References 53 publications
10
218
2
Order By: Relevance
“…Astrocytes play an important role in the brain physiology, as well as in learning and memory formation [ 59 ]. Reactive astrogliosis are dynamic and heterogeneous in their location, subtypes, hypertrophy/proliferation, and upregulation of different markers such as GFAP, vimentin, nestin, MAO-B, and gamma-amino butyric acid [ 60, 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes play an important role in the brain physiology, as well as in learning and memory formation [ 59 ]. Reactive astrogliosis are dynamic and heterogeneous in their location, subtypes, hypertrophy/proliferation, and upregulation of different markers such as GFAP, vimentin, nestin, MAO-B, and gamma-amino butyric acid [ 60, 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, our data indicate that microanatomical changes may cause learning and spatial memory perturbation, expanding the view that memory formation is not exclusively related to neurons, but also involves glial cells (Azevedo et al, 2009;Kol et al, 2020). No direct correlation related learning and morphology, but suggested different astrocytes profiles.…”
Section: Discussionmentioning
confidence: 53%
“…No direct correlation related learning and morphology, but suggested different astrocytes profiles. Indeed, astrocytes may contribute to learning and memory as signaling centers, and by giving structural and metabolic support, they regulate synaptic activity and recruit energetic resources for memory consolidation (Zorec et al, 2015;Kol et al, 2020). In particular, it has been demonstrated that hippocampusbased contextual memory process alters the morphology of astrocytes in the dentate gyrus originating a novel cell morphofunctional status, which is different from that of reactive states (Choi et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Another finding in ITPR2 −/− mice was increased frequency of sleep spindles during IS sleep, which may cause impaired memory consolidation (Bojarskaite et al, 2020). This finding may provide a mechanistic explanation for impaired remote memory in ITPR2 −/− mice discussed above (Pinto-Duarte et al, 2019) or for impaired remote memory in consequence of manipulation of astroglia Ca 2+ dynamics using the humanized G i protein-coupled muscarinic receptor type 4 DREADD (hM4Di) discussed below (Kol et al, 2020). Bojarskaite et al (2020) also found considerably reduced delta electrocorticogram power during NREM sleep in ITPR2 −/− mice, which indicates reduced sleep pressure, which is consistent with the first study that reported astrocyte control of sleep pressure and the impact of sleep deprivation (Halassa et al, 2009).…”
Section: Consequences Of Deletion Of Ip 3 R2 Signalingmentioning
confidence: 96%